A CRN simulation for emission pollutants prediction in lean premixed gas turbine combustor. - Hao, Nguyen Thanh (Asean Engineering Journal)
This study presents the use of a new CRN (Chemical Reactor Network) model and non-uniform injectors to predict the emission pollutant in the lean premixed gas turbine combustor. The CRN uses the information from the CFD (Computational Fluid Dynamics) combustion analysis with two injectors of CH4-air mixture. The experiment and the modeling focus on the output of the turbine combustor and the optimized fuel load. The injectors of CH4-air mixture have different lean equivalence ratio, and they control the fuel flow to stabilize the combustion and adjust the combustor's equivalence ratio. The non-uniform injector is applied to improve the burning process of the turbine combustor. The results of the new CRN emission predictions for the gas turbine combustor show very good agreement with the experimental data from Korea Electric Power Research Institute. The new CRN model is a valuable tool in the evaluation of the pollution formation and the performance of the turbine combustor systems.